Out-of-Pocket Expenses for Maternity Care in Rural Bangladesh: A Public-Private Comparison. (April 2013) - Rahman, Md. Moshiur; Rob, Ubaidur; Noor, Forhana Rahman; Bellows, Benjamin
Out-of-pocket expenses incurred by women for availing maternal healthcare services at public and private health facilities in Bangladesh were examined using a baseline household survey evaluating the impact of demand side financing vouchers on utilization and service delivery for maternal healthcare. The survey was conducted in 2010 among 3, 300 women who gave birth in the previous 12 months from the start of data collection. Information on costs incurred to receive antenatal, delivery, and postnatal care services was collected. Findings reveal that the majority of women reported paying out-of-pocket expenses for availing maternal healthcare services both at public and private health facilities. Out-of-pocket expenses include registration, consultation, laboratory examination, medicine, transportation, and other associated costs incurred for receiving maternal healthcare services. On average, women paid US3.60 out-of-pocket expenses for receiving antenatal care at public health facilities and US12.40 at private health facilities. Similarly, women paid one and half times more for normal (US42.30) and cesarean deliveries (US136.20) at private health facilities compared to public health facilities. On the other hand, costs for postnatal care services did not vary significantly between public and private health facilities. Utilization of maternal healthcare services can be improved if out-of-pocket expenses can be minimized. At the same time, effective demand generation strategies are necessary to encourage women to utilize health facilities.